A prospective observational study and survival pattern of organo phosphorous poisoning patients with intensive care treatment in a tertiary care hospital - Roby, Kanamala Arun Chand; Srinivas, B.; Sandeep, B.; Reddy, S. Nikhil; Yadav, M. Ajay; Harinadha Baba, Kudipudi (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Organophosphate poisoning is poisoning due to organophosphates (OP’s), used in insecticides, medications and nerve agents. It occurs mostly during suicide attempts in the farming areas, developing world and less by accident. The study is to evaluate the drugs used, respiratory conditions, complications occurred during course of treatment. Methods: This was a prospective observational study conducted for 9 months in a tertiary care hospital. The study was conducted in a 500 bedded tertiary care hospital in an intensive care unit. The study was conducted for nine months (September 2016 - May 2017). Results: A total of 234 patients who had consumed OPP with known and unknown agents were admitted in the emergency department. Out of which 180 males and 54 females. Conclusions: This study concluded that the patients consumed poison is mainly due to mental disturbances and financial problems. The stress and burden on the life will shows the effect after consumption, the maximum people suffer with respiratory problems due to poison consumption. If the government should take the measures to avoid consumption of poison and availability of poison to the public may overcome the complications and reduce the deaths due to poison.